(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The paper focuses on the main conceptual issues (classifications, terminology, methodology) relating to the phenomenon of the degeneration of contemporary democracies that have attracted the attention of different social sciences in recent years. It begins with a reconstruction of the main cultural trends of democracy (classical, liberal, socialist, social, radical, and so on) then continues by exploring the current debate. The debate focuses on some leading categorizations: illiberal democracies, authoritarian constitutionalism and populist constitutionalism.